PHYTOCHEMICAL ANALYSIS AND IN VITRO EFFECTS OF Solanum dasyphyllum FRUIT EXTRACT ON EIMERIA IN BROILERS, JOS, NIGERIA - Akpojosevbe, E. J.; Sawa, F. B. J.; Buba, T. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the phytochemical composition, gas chromatography-mass spectrometry (GC-MS) analysis and in vitro anticoccidial effects of Solanum dasyphyllum fruit extract on Eimeria species in broilers. Fresh fruits were collected from the National Veterinary Research Institute (NVRI), Jos, Plateau State, Nigeria, authenticated, air-dried, pulverized, and extracted using 70% ethanol. Stock solutions (100 mg/mL) and lower concentrations (50 and 25 mg/mL) were prepared for in vitro testing. Phytochemical screening and GC-MS analysis were conducted. Mixed Eimeria oocysts were obtained from NVRI Parasitology Division. In vitro assays evaluated oocyst sporulation (24–48 h) and sporozoite viability (72 h). Phytochemical screening revealed saponins, tannins, flavonoids, alkaloids, quinones, coumarins, phenones, and steroids/triterpenoids. GC-MS detected six major compounds, including 9-octadecenoic acid methyl ester (37.3%). In vitro, 50 and 100 mg/mL extract completely inhibited oocyst sporulation at 48 h, while 25 mg/mL reduced sporulated oocysts from 80.67 ± 16.9 to 6.33 ± 3.5. Sporozoite viability decreased to 7.33–8.67 with non-viable counts increasing to 100.67–141.67, comparable to Amprolium. In conclusion, S. dasyphyllum fruit extract contains bioactive compounds with potent anticoccidial activity of S. dasyphyllum fruit extract can serve as a natural alternative for coccidiosis management in broilers, and further studies should investigate its safety and efficacy in large-scale trials.